Implementing Active Learning to Increase Student's Learning Interest in Islamic Religious Education - Ijudin Ijudin; Yasya Fauzan Wakila; Anton Anton (Jurnal Pendidikan Islam, 2022)
This study aims to investigate the implementation learning model called Paikem Gembrot to increase students' learning interest. It is quantitative in nature and applies pre-experiential one group pretest-posttest experiments. The results show that the learning model Paikem Gembrot was tested for its validity and reliability. There were 10 statement items categorized as valid with the score 0.47. The learning interest questionnaire contained 13 statement items categorized as valid with the score 0.78. The results of the normality test for pretest of the experimental class was 72 and the control class was 74. The results of normality test for posttest for the experimental class score was 95 and the control class was 88. The hypothesis testing indicates that the value of tcount is 4.45 and it is greater than ttable, namely 2.70. It means that the learning model Paikem Gembrot can increase students' learning interest in learning Islamic religious education subject.